Pornography, sexual socialization, and satisfaction among young men - Štulhofer, Aleksandar (Array, 2010)
In spite of a growing presence of pornography in contemporary life, little is known about its potential effects on young people's sexual socialization and sexual satisfaction. In this article, we present a theoretical model of the effects of sexually explicit materials (SEM) mediated by sexual scripting and moderated by the type of SEM used. An on-line survey dataset that included 650 young Croatian men aged 18-25 years was used to explore empirically the model. Descriptive findings pointed to significant differences between mainstream and paraphilic SEM users in frequency of SEM use at the age of 14, current SEM use, frequency of masturbation, sexual boredom, acceptance of sex myths, and sexual compulsiveness. In testing the model, a novel instrument was used, the Sexual Scripts Overlap Scale, designed to measure the influence of SEM on sexual socialization. Structural equation analyses suggested that negative effects of early exposure to SEM on young men's sexual satisfaction, albeit small, could be stronger than positive effects. Both positive and negative effects—the latter being expressed through suppression of intimacy—were observed only among users of paraphilic SEM. No effect of early exposure to SEM was found among the mainstream SEM users. To counterbalance moral panic but also glamorization of pornography, sex education programs should incorporate contents that would increase media literacy and assist young people in critical interpretation of pornographic imagery.